Public Transport Operations After Lockdown: How to Make It Happen? - Suman, Hemant K. (Trans Indian Natl. Acad. Eng., 2020)
Lockdown in cities across the globe has imposed severe travel restrictions to limit the spread of Coronavirus disease. The travel behavior and operations will not be the same as before due to requirements such as physical (social) distancing. This study analyzes the resulting shortage in supply of public transport (buses) that will likely widen the existing gap between demand and supply. In this work, system optimization models are developed to efficiently reallocate the bus fleet to routes for different levels of physical distancing gaps and travel demand. The proposed models are applied to a real-life network of 34 bus routes of Delhi, considering three types of scenarios: current, practical, and ideal. In the practical scenarios, the additional, idling bus fleets can be allocated to the routes efficiently while maintaining physical distancing. The results show that the Business-as-Usual (BAU) scenario involving the current allocation approach will make it impossible to use public buses even if the bare minimum physical distancing has to be maintained. Further, the models proposed in the study significantly improve the key performance indicators for all scenarios.